Highly Selective Perfluoroalkylation of Unsaturated Molecules upon Photoirradiation in BTF as an Organic/Fluorous Hybrid Solvent - Tamai, Taichi; Sonoda, Motohiro; Ogawa, Akiya (Journal of Applied Solution Chemistry and Modeling, 2013)
Benzotrifluoride (BTF), an eco-friendly solvent, can dissolve many organic and fluorous molecules because of the organic and fluorous motifs in its structure. Using BTF as solvent, we have developed a series of reactions for perfluoroalkylation of various unsaturated compounds upon photoirradiation with a Xe lamp through Pyrex. For example, alkynes, allenes, vinylcyclopropanes, isocyanides, diynes, dienes, and enynes successfully undergo regioselective perfluoroalkyliodination, perfluoroalkylselenation, and perfluoroalkyltelluration in BTF. In addition, the present photoinitiation procedure can be applied to trifluoromethylation